2019
DOI: 10.1021/acs.jpclett.8b03717
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Mechanism of Broadband Emission in Metal Halide Perovskites

Abstract: Broadband emission is attributed to the formation of self-trapped excitons (STEs) due to the strong electron−phonon coupling. Interestingly, it has been observed in only certain three-dimensional and low-dimensional metal halide perovskites. Here, we show by density functional theory calculation that a low electronic dimensionality is a prerequisite for the formation of STE and, therefore, broadband emission. We further show that multiple STE structures exist in each perovskite exhibiting broadband emission. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
276
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(299 citation statements)
references
References 33 publications
23
276
0
Order By: Relevance
“…30 We also observe self-trapped exciton resonances (small polarons) in PL centered at energies <2.0 eV that are hypothesized to be the cause of the broad, low-temperature, lowerenergy PL resonance present in many 2DHPs including those here in (PEA)2PbI4, 2-F, 2-Cl, and 2-Br ( Figure S11). [31][32][33] In 2-Cl, the self-trapped exciton resonance is centered at 1.9257(6) eV and exhibits triexponential kinetics with lifetimes of 29.6(2) ns, 301 (1) Compared to (PEA)2PbI4 and 2-Cl, 2-F exhibits more complex behavior in steady-state and time-resolved spectra. In absorption at 10 K ( Figure 3A and Table S10), we observe three sharp Lorentzian resonances (green, orange, red), and another resonance (yellow) of similar width is included for a good fit.…”
Section: Resultsmentioning
confidence: 99%
“…30 We also observe self-trapped exciton resonances (small polarons) in PL centered at energies <2.0 eV that are hypothesized to be the cause of the broad, low-temperature, lowerenergy PL resonance present in many 2DHPs including those here in (PEA)2PbI4, 2-F, 2-Cl, and 2-Br ( Figure S11). [31][32][33] In 2-Cl, the self-trapped exciton resonance is centered at 1.9257(6) eV and exhibits triexponential kinetics with lifetimes of 29.6(2) ns, 301 (1) Compared to (PEA)2PbI4 and 2-Cl, 2-F exhibits more complex behavior in steady-state and time-resolved spectra. In absorption at 10 K ( Figure 3A and Table S10), we observe three sharp Lorentzian resonances (green, orange, red), and another resonance (yellow) of similar width is included for a good fit.…”
Section: Resultsmentioning
confidence: 99%
“…64 Despite being formed by a continuous metal halide network, the presence of alternating AgCl 6 and InCl 6 octahedra brakes the continuity of orbital overlap resulting in a reduced 0D-like electronic dimensionality. 65 Charge confinement within single octahedral units was further enhanced by means of Na + and Bi 3+ doping. 64 Hexamethylentetrammonium (HMTA) was used for the synthesis of (HMTA) 3 Pb 2 Br 7 which forms a bulk assembly of 1D lead bromide nanotubes: six dimers of face sharing lead bromide octahedra (Pb 2 Br 9 5-) connect at the corners forming a ring with inner radius of 4Å which extends in one dimension to form the nanotube (Fig.…”
Section: Broadband Emission In Low Dimensional Perovskitesmentioning
confidence: 99%
“…96 Recently, X. Wang et al showed by means of density functional theory calculations that reduced electronic dimensionality plays a crucial role in the formation of self-trapped excitons. 65 Although several species can form, it was proposed that self-trapped excitons connected to Jahn−Teller-like octahedral distortion give the main contribution to the broadband luminescence, 65 while all other types of self-trapped excitons act as non-radiative recombination channels. The existence of such two competing mechanisms suggests that Jahn−Teller-like self-trapped excitons must be promoted while suppressing non-Jahn−Teller-like states in order to obtain high photoluminescence quantum yields.…”
Section: Origin Of Broadband Emissionmentioning
confidence: 99%
“…Admittedly, the possibility of energy transfer from free exciton (FE) to Ho 3+ cannot be entirely dismissed. However, on account of the transient transformation of FE to STE accomplished within several hundred femtoseconds, finishing in several hundred femtoseconds as well is the prerequisite for an effective energy transfer process from FE to Ho 3+ …”
mentioning
confidence: 99%